MANUFACTURE OF BODIES, BOOM AND BASE FRAME FOR MINI FLOOR CRANES WITH A LIFTING CAPACITY OF 2 TONS - Antonius Adi Soetopo; Rani Nopriyanti; Ahmad Maulana Mustopa; Faiq Surya Ramadhani (Department of Mechanical Engineering, Universitas Sultan Ageng Tirtayasa, 2026)
Operational efficiency in small and medium scale manufacturing industries and machine maintenance workshop heavily depends on the smooth flow of heavy material handling. The use of precise lifting equipment is crucial olxtogel for ensuring workplace safety and production activities. However, in work areas where speace is limited or movement is restricted, the use of large lifting equipment is impractical and economically unfeasible. This study aims to design and build mini floor crane with a lifting capacity of 2 tons, focushing on the design and fabrication of the body, boom and base frame structures. The research method combines manual mathematical calculation to determine bending stress and deflection in the boom and base, which is then validated using Finite Element Analysis (FEA) to identify critical points in the structure. Productivity analysis demonstrates that the use lifting equipment is significantly more advantageous both technically and economically, with increased operational efficiency compored to methods.